Tana Luwu’s Local Environmental Wisdom (Vandana Shiva’s Ecofeminism Perspective) - Syahruddin Syahruddin; Sapruddin Sapruddin; Andi Batara Indra; Fajrul Ilmy Darussalam; Emiyanti Emiyanti (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
This study aims to determine the form and practice of Luwu's local wisdom in Vandana Shiva's ecofeminism perspective. This study used descriptive qualitative methods focusing on the indigenous peoples of Kalotok, Kanan Dede, and Komba. The study found that: (1) the forms of local wisdom of Luwu in the perspective of ecofeminism as follows; Tudang sipulung (round-down sitting), pesta panen (harvesting party), and tomakaka perempuan (local-noble female); (2) Local wisdom practices of Luwu in the perspective of ecofeminism have been embodied in deliberation and negotiation between community leaders for some events. The practices are the planting season, when someone violates customs, cutting down trees for building a house, ‘pesta panen’ (harvest celebrations by the community), ‘makan bersama’ (congregational feast between community groups), the involvement of women as tomakaka (noble person), and the existence of women's farmer groups.